2009
DOI: 10.1007/s10616-009-9229-5
|View full text |Cite
|
Sign up to set email alerts
|

Different expression levels of TNF receptors on the rheumatoid synovial macrophages derived from surgery and a synovectomy as detected by a new flow cytometric analysis

Abstract: TNFa plays a crucial role in the pathogenesis of rheumatoid arthritis. It is very important to examine the expression of the TNF receptors, the ligand of TNFa. In this study, we developed a triplecolor flow cytometric analysis using CD45 and CD14 monoclonal antibodies to simply detect the expression of the TNF receptors on the heterogeneous rheumatoid synovial cells. Using this system, we detected a higher population of macrophages and a greater TNF receptor expression on the synovial macrophages derived from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“… 33 Synoviocytes are known to express gp130 but not IL-6R, and can therefore only respond to IL-6 in the presence of sIL-6R. 31 We previously observed that chondrocytes express gp130, IL-6R, and sIL-6R. 34 Here, we further show that HIF-2α upregulates IL-6R in chondrocytes but not FLS, suggesting that FLS-derived IL-6 may critically mediate the functions of chondrocytes.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“… 33 Synoviocytes are known to express gp130 but not IL-6R, and can therefore only respond to IL-6 in the presence of sIL-6R. 31 We previously observed that chondrocytes express gp130, IL-6R, and sIL-6R. 34 Here, we further show that HIF-2α upregulates IL-6R in chondrocytes but not FLS, suggesting that FLS-derived IL-6 may critically mediate the functions of chondrocytes.…”
Section: Discussionmentioning
confidence: 49%
“…29 In addition, an anti-IL-6 antibody was shown to inhibit RA in an experimental mouse model, and the humanized anti-IL-6 receptor antibody, tocilizumab, is used as an immunosuppressive drug in RA patients. 30 TNF-α can bind to two specific receptors, TNFR1 and TNFR2, which are both expressed in RA synovium 31 and OA cartilage. 32 Here, we show that HIF-2α upregulates TNFR2 (encoded by Tnfrsf1b ) in FLS but not chondrocytes, suggesting that chondrocyte-derived TNF-α may critically mediate the functions of FLS.…”
Section: Discussionmentioning
confidence: 99%